2021
DOI: 10.1109/tnsre.2021.3128878
|View full text |Cite
|
Sign up to set email alerts
|

Spiking Characteristics of Network-Mediated Responses Arising in Direction-Selective Ganglion Cells of Rabbit and Mouse Retinas to Electric Stimulation for Retinal Prostheses

Abstract: To restore the sight of individuals blinded by outer retinal degeneration, numerous retinal prostheses have been developed. However, the performance of those implants is still hampered by some factors including the lack of comprehensive understanding of the electrically-evoked responses arising in various retinal ganglion cell (RGC) types. In this study, we characterized the electrically-evoked network-mediated responses (hereafter referred to as electric responses) of ON-OFF direction-selective (DS) RGCs in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Among all RGCs classified by their light responses, the electrically-evoked responses of representative 6 cells of each RGC type were shown (Figures 4A-C), which showed the highest peak firing rate (PFR) in ON and OFF types (Figures 4A, B). The spiking patterns of those RGCs seemed largely similar to those reported earlier by our group from the healthy retinas (Tsai et al, 2009;Fried, 2015, 2016b;Im et al, 2018;Lee and Im, 2019;Otgondemberel et al, 2021), but minor deviations were observed in responses of ON and DS RGCs. For example, most ON RGCs showed two bursts of spikes which were separated by silent periods (n = 12/14; Figure 4Ai), while some ON RGCs showed three bursts (n = 2/14; Figure 4Aii).…”
Section: Electrically-evoked Response Patterns Of Individual Rd8supporting
confidence: 86%
See 4 more Smart Citations
“…Among all RGCs classified by their light responses, the electrically-evoked responses of representative 6 cells of each RGC type were shown (Figures 4A-C), which showed the highest peak firing rate (PFR) in ON and OFF types (Figures 4A, B). The spiking patterns of those RGCs seemed largely similar to those reported earlier by our group from the healthy retinas (Tsai et al, 2009;Fried, 2015, 2016b;Im et al, 2018;Lee and Im, 2019;Otgondemberel et al, 2021), but minor deviations were observed in responses of ON and DS RGCs. For example, most ON RGCs showed two bursts of spikes which were separated by silent periods (n = 12/14; Figure 4Ai), while some ON RGCs showed three bursts (n = 2/14; Figure 4Aii).…”
Section: Electrically-evoked Response Patterns Of Individual Rd8supporting
confidence: 86%
“…Another distinct populational features of the rd8 RGCs was also observed in DS RGCs: since the responses of wt DS RGC were already investigated by creating scatter plots of spike counts in our earlier work (Otgondemberel et al, 2021), we similarly plotted spike counts as a function of average DSI (DSI AVG ) (Figure 6A). Spike counts of the early responses in the rd8 DS RGCs yielded a weak negative correlation with the DSI AVG , which was somewhat analogous to wt ones (r = −0.15 vs. −0.57 for rd8 vs. wt; see Otgondemberel et al, 2021 for wt data).…”
Section: Correlations Between Response Magnitudes To Electric Vs Ligh...mentioning
confidence: 86%
See 3 more Smart Citations